2014
DOI: 10.1074/jbc.r114.595439
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc and the Epigenetic Regulation of Gene Expression

Abstract: O-GlcNAcylation is an abundant nutrient-driven modification linked to cellular signaling and regulation of gene expression. Utilizing precursors derived from metabolic flux, O-GlcNAc functions as a homeostatic regulator. The enzymes of O-GlcNAc cycling, OGT and O-GlcNAcase, act in mitochondria, the cytoplasm, and the nucleus in association with epigenetic "writers" and "erasers" of the histone code. Both O-GlcNAc and O-phosphate modify repeats within the RNA polymerase II C-terminal domain (CTD). By communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
118
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 99 publications
(154 reference statements)
3
118
0
Order By: Relevance
“…O-GlcNAc transferase (OGT) utilizes UDP-GlcNAc as a high energy donor substrate and the ␤-N-acetylglucosaminidase or O-GlcNAcase (OGA) removes GlcNAc from protein substrates (35)(36)(37). Physiologically, O-GlcNAcylation likely plays significant causal roles in type 2 diabetes and cancer.…”
mentioning
confidence: 99%
“…O-GlcNAc transferase (OGT) utilizes UDP-GlcNAc as a high energy donor substrate and the ␤-N-acetylglucosaminidase or O-GlcNAcase (OGA) removes GlcNAc from protein substrates (35)(36)(37). Physiologically, O-GlcNAcylation likely plays significant causal roles in type 2 diabetes and cancer.…”
mentioning
confidence: 99%
“…O-GlcNAcylation plays an important role in controlling transcription. O-GlcNAc regulates gene transcription by directly modifying transcription factors/cofactors or RNA Pol II CTD (33) or by altering how the activity of these factors is modulated by other post-translational modifications (39). A previous study by Ranuncolo et al (33) suggested that an O-GlcNAcylation cycle on RNA Pol II CTD occurs at gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…The role of O-GlcNAc in epigenetics is reviewed in detail in Ref. 98, whereas a few specific examples potentially relevant to cancer will be noted here.…”
Section: O-glcnac and Cancer Cell Epigeneticsmentioning
confidence: 99%